Uptake of prevention of mother-to-child transmission cascade services in Burkina Faso between 2013 and 2020: are we on the right track? - Lucresse Corine Fassinou; Joël Ouoba; Calypse Ngwasiri; Issa Romba; Wedminere Noëlie Zoungrana-Yameogo; Fidèle Bakiono; Isidore Tiandiogo Traoré; Hervé Hien; Nicolas Nagot; Fati Kirakoya-Samadoulougou (BMC, 2023)
Abstract Background The use of services to prevent mother-to-child transmission (PMTCT) of the human immunodeficiency virus (HIV) remains a serious challenge in sub-Saharan Africa. In the last decade, Burkina Faso has implemented numerous policies to increase the use of PMTCT services by pregnant women and their partners, as well as children. This study assesses trends in the uptake of PMTCT services in Burkina Faso from 2013 to 2020 in order to study the progress and gaps in achieving the national and international targets set for 2020. Methods A repeated cross-sectional analysis was performed using data extracted from district health information software version 2. Percentages were computed for each PMTCT indicator and comparisons between the years were made using a chi-square test for trends with a significance threshold of 5%. Regions were not compared with each other. Results The proportion of pregnant women who were tested and received their results significantly increased from 47.9% in 2013 to 84.6% in 2020 (p value < 0.001). Of the 13 regions in the country, only 1 region met the 95% national targets whereas, 6 regions met the 90% international targets for this indicator. The proportions of HIV-positive women receiving antiretroviral therapy (ART) increased from 90.8% in 2013 to 100% in 2020. In the same period, the proportion of exposed infants who received antiretroviral prophylaxis increased from 64.3% in 2013 to 86.8% in 2020. Only 3 regions reached the national and international targets for this indicator. A positive trend was also observed for the indicator related to screening at 2 months or later of exposed infants using Polymerase Chain Reaction (PCR) technic; with the rate rising from 7.4% in 2013 to 75.7% in 2020. However, for this indicator, the national and international targets were not achieved considering the national and regional settings. Concerning the women's partners, the proportion of those who tested for HIV increased from 0.9% in 2013 to 4.5% in 2020, with only 1 region that fully met the national target of 10% in 2020. The prevalence of HIV in this particular group was 0.5% in 2020. Conclusions PMTCT indicators show an increase from 2013 to 2020 but with a strong disparity between regions. National and international targets have not been achieved for any indicator; except for those related to women receiving ART. Strengthening strategies to effectively engage women and their partners on the use of PMTCT cascade services could help reduce mother-to-child transmission in Burkina Faso.